Critical Discourse Analysis of Online News on the Sibolga Flood in CNN Indonesia and Liputan6 - Esra Delima Hutabarat; Vercelly Hot Taruli Manik; Kesmi Veronika Manik Manik; Partohap Sihombing (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This study examines how the Sibolga flood is represented in Indonesian online news media by applying Norman Fairclough’s Critical Discourse Analysis (CDA). Using a qualitative approach, the data consist of two online news articles reporting the same flood event, published by CNN Indonesia and Liputan6 within the same time period. The analysis follows Fairclough’s three-dimensional framework, encompassing textual analysis, discursive practice, and social practice. The findings reveal notable differences in the linguistic and discursive strategies employed by the two media outlets. CNN Indonesia tends to emphasize severity, casualties, and urgency through evaluative lexical choices and dramatic headlines, positioning the flood as a major humanitarian crisis. In contrast, Liputan6 focuses more on infrastructural recovery and institutional responses, framing the disaster within a narrative of control and normalization. These differing representations reflect distinct ideological orientations and power relations, particularly in relation to state institutions and public audiences. The study concludes that online disaster reporting is not neutral but functions as a discursive site where meaning, responsibility, and social reality are constructed. This research contributes to Critical Discourse Analysis and media studies by highlighting how language shapes public understanding of disasters in Indonesian online news.